Unrelenting change, innovation, and risk : forging the next generation of community colleges - Phelan, Daniel J., 1959- (Rowman and Littlefield, 2016)
In this book, thirty-five year veteran Dan Phelan shares key insights from his personal and professional journey as a transformational, entrepreneurial community college leader. The book's wisdom and insights are amplified by observations gleaned from interviews and visits with dozens of leading practitioners. Drawing upon his sailing experiences, Phelan argues that leaders should stop playing it safe in the harbor because the real gains driving institutional and student success are found in uncharted waters. Unrelenting Change, Disruptive Innovation, and Risk: Forging the Next Generation of C.